PENCAPAIAN KOMPETENSI LITERASI NUMERASI SISWA DENGAN MODEL PROBLEM BASED LEARNING - Yanti Nazmai Ekaputri; Veni Veni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
Numerical literacy is an ability that needs and is very important to improve. So it is necessary to do research to improve students' numeracy literacy skills with the PBL model. This research is a quantitative research. The research method is pretest-posttest design with purposive sampling technique. Samples were selected randomly from the population. The population of this study were high school students in the South coast district. The sample was selected from schools that have A accreditation because seen from the data obtained, there are more schools that are accredited B and others. The conclusion is obtained by looking at the results of the given numeracy literacy skills which have previously been validated by experts in their fields. The conclusion obtained is that the achievement of the control class using PBL can effectively improve students' numeracy literacy skills, while the control class has not provided an effective increase in students' numeracy literacy abilities.